Activation of Cdc42 is necessary for sustained oscillations of Ca2+ and PIP2 stimulated by antigen in RBL mast cells - Marcus M. Wilkes; Joshua D. Wilson; Barbara Baird; David Holowka (Biology Open, 2014)
Antigen stimulation of mast cells via FcεRI, the high-affinity receptor for IgE, triggers a signaling cascade that requires Ca2+ mobilization for exocytosis of secretory granules during the allergic response. To characterize the role of Rho GTPases in FcεRI signaling, we utilized a mutant RBL cell line, B6A4C1, that is deficient in antigen-stimulated Cdc42 activation important for these processes. Recently the importance of stimulated intracellular oscillations has emerged, and we find that B6A4C1 cells exhibit severely attenuated Ca2+ oscillations in response to antigen, which are restored to wild-type RBL-2H3 levels by expression of constitutively active Cdc42 G12V or by a GEF for Cdc42, DOCK7, but not when the C-terminal di-arginine motif of active Cdc42 is mutated to di-glutamine. We found that antigen-stimulated FcεRI endocytosis, which occurs independently of Ca2+ mobilization, is also defective in B6A4C1 cells, and Cdc42 G12V reconstitutes this response as well. Thus, activation of Cdc42 occurs prior to and is critical for antigen-stimulated pathways leading separately to both Ca2+ mobilization and receptor endocytosis. Accounting for these downstream functional consequences, we show that Cdc42 G12V reconstitutes antigen-stimulated oscillations of phosphatidylinositol 4,5-bisphosphate (PIP2) at the plasma membrane in mutant B6A4C1 cells, pointing to Cdc42 participation in the regulation of stimulated PIP2 synthesis.